On the Koszul cohomology of canonical and Prym‐canonical binary curves. (19th May 2013) - Colombo, Elisabetta; Frediani, Paola
Abstract : In this paper we study Koszul cohomology and the Green and Prym–Green conjectures for canonical and Prym‐canonical binary curves. We prove that, if property N p holds for a canonical or a Prym‐canonical binary curve of genus g, then it holds for a generic canonical or Prym‐canonical binary curve of genus g + 1. We also verify the Green and Prym–Green conjectures for generic canonical and Prym‐canonical binary curves of low genus (6 ⩽ g ⩽ 15, g ≠ 8 for Prym‐canonical and 3 ⩽ g ⩽ 12 for canonical).